Auditory Perception of Sound Sources - Yost, William A.; Popper, Arthur N.; Fay, Richard R.; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
Auditory Perception of Sound Sources covers higher-level auditory processes that are perceptual processes. The chapters describe how humans and other animals perceive the sounds that they receive from the many sound sources existing in the world. This book will provide an overview of areas of current research involved with understanding how sound-source determination processes operate. This book will focus on psychophysics and perception as well as being relevant to basic auditory research. Contents: Perceiving Sound Sources: An Overview William A. Yost Human Sound Source Identification Robert A. Lutfi Size Information in the Production and Perception of Communication Sounds Roy D. Patterson, David R. R. Smith, Ralph van Dinther, and Tom Walters The role of memory in auditory perception Laurent Demany, and Catherine Semal Auditory Attention and Filters Ervin R. Hafter, Anastasios Sarampalis, and Psyche Loui Informational masking Gerald Kidd Jr., Christine R. Mason, Virginia M. Richards, Frederick J. Gallun, and Nathaniel I. Durlach Effects of harmonicity and regularity on the perception of sound sources Robert P. Carlyon, and Hedwig E. Gockel Spatial Hearing and Perceiving Sources Christopher J. Darwin Envelope Processing and Sound-Source Perception Stanley Sheft Speech as a Sound Source Andrew J. Lotto, and Sarah C. Sullivan Sound Source Perception and Stream Segregation in Non-human Vertebrate Animals Richard R. Fay About the editors: William A. Yost, Ph.D., is Professor of Psychology, Adjunct Professor of Hearing Sciences of the Parmly Hearing Institute, and Adjunct Professor of Otolaryngology at Loyola University of Chicago. Arthur N. Popper is Professor in the Department of Biology and Co-Director of the Center for Comparative and Evolutionary Biology of Hearing at the University of Maryland, College Park. Richard R. Fay is Director of the Parmly Hearing Institute and Professor of Psychology at Loyola University of Chicago. About the series: The Springer Handbook of Auditory Research presents a series of synthetic reviews of fundamental topics dealing with auditory systems. Each volume is independent and authoritative; taken as a set, this series is the definitive resource in the field.
Perceiving Sound Sources -- Human Sound Source Identification -- Size Information in the Production and Perception of Communication Sounds -- The Role of Memory in Auditory Perception -- Auditory Attention and Filters -- Informational Masking -- Effects of Harmonicity and Regularity on the Perception of Sound Sources -- Spatial Hearing and Perceiving Sources -- Envelope Processing and Sound-Source Perception -- Speech as a Sound Source -- Sound Source Perception and Stream Segregation in Nonhuman Vertebrate Animals.
Keywords: Medicine; Neurosciences; Otorhinolaryngology; Neuropsychology; Cognitive psychology; Biomedicine; Neurosciences; Otorhinolaryngology; Neuropsychology; Cognitive Psychology; Electronic books